Manitoba-oculo-tricho-anal (MOTA) syndrome is caused by mutations in FREM1. Issue 6 (20th April 2011) - Slavotinek, Anne M; Baranzini, Sergio E; Schanze, Denny; Labelle-Dumais, Cassandre; Short, Kieran M; Chao, Ryan; Yahyavi, Mani; Bijlsma, Emilia K; Chu, Catherine; Musone, Stacey; Wheatley, Ashleigh; Kwok, Pui-Yan; et al.
Abstract : Background: Manitoba-oculo-tricho-anal (MOTA) syndrome is a rare condition defined by eyelid colobomas, cryptophthalmos and anophthalmia/microphthalmia, an aberrant hairline, a bifid or broad nasal tip, and gastrointestinal anomalies such as omphalocele and anal stenosis. Autosomal recessive inheritance had been assumed because of consanguinity in the Oji-Cre population of Manitoba and reports of affected siblings, but no locus or cytogenetic aberration had previously been described. Methods and results: This study shows that MOTA syndrome is caused by mutations in FREM1, a gene previously mutated in bifid nose, renal agenesis, and anorectal malformations (BNAR) syndrome. MOTA syndrome and BNAR syndrome can therefore be considered as part of a phenotypic spectrum that is similar to, but distinct from and less severe than, Fraser syndrome. Re-examination of Frem1 bat/bat mutant mice found new evidence that Frem1 is involved in anal and craniofacial development, with anal prolapse, eyelid colobomas, telecanthus, a shortened snout and reduced philtral height present in the mutant mice, similar to the human phenotype in MOTA syndrome. Conclusions: The milder phenotypes associated with FREM1 deficiency in humans (MOTA syndrome and BNAR syndrome) compared to that resulting from FRAS1 and FREM2 loss of function (Fraser syndrome) are also consistent with the less severe phenotypes resulting from Frem1 loss of function in mice. Together, Fraser, BNAR and MOTA syndromes constitute a clinically overlapping group of FRAS–FREM complex diseases.